2015
DOI: 10.1111/sji.12311
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Transfected with a DNA Construct Encoding Tumour‐associated Antigen Epitopes Induce a Cytotoxic Immune Response Against Autologous Tumour Cells in a Culture of Mononuclear Cells from Colorectal Cancer Patients

Abstract: Significant effort has been devoted to developing effective cancer vaccines based on dendritic cells (DCs) loaded with various tumour antigens, including DNA constructs that carry sequences of tumour-associated antigens (TAAs). Such vaccines efficiently and selectively activate the T cell immune response. In this study, we describe a method to induce an antitumour immune response in mononuclear cell (MNC) cultures from colorectal cancer patients using DNAtransfected DCs encoding TAA epitopes of carcinoembryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…To date, there are a number of approaches for generating DCs in vitro, including preparation of DCs from peripheral blood monocytes and bone marrow progenitors (CD34 + cells) (18). Furthermore, a wide range of factors may be used for differentiation and maturation of DCs (GM-CSF, IL-4, interferon-α, IL-2, IL-6, IL-15, TGF-α, stem cell factor, FLT-3 ligand and prostaglandin E2) that may facilitate, in a combination or individually, the generation of DCs from monocytes or CD34 + cells (19)(20)(21)(22)(23). The present study suggested that there is some danger in using numerous factors for differentiation and maturation of DCs that can lead to the production of DC subsets with a variety of phenotypes and functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are a number of approaches for generating DCs in vitro, including preparation of DCs from peripheral blood monocytes and bone marrow progenitors (CD34 + cells) (18). Furthermore, a wide range of factors may be used for differentiation and maturation of DCs (GM-CSF, IL-4, interferon-α, IL-2, IL-6, IL-15, TGF-α, stem cell factor, FLT-3 ligand and prostaglandin E2) that may facilitate, in a combination or individually, the generation of DCs from monocytes or CD34 + cells (19)(20)(21)(22)(23). The present study suggested that there is some danger in using numerous factors for differentiation and maturation of DCs that can lead to the production of DC subsets with a variety of phenotypes and functions.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cell lysates, tumor cell RNA, recombinant proteins of tumor-associated antigens, and DNA constructs encoding tumor-associated antigens have been used as antigens (21,30,31). Loading DCs with a tumor lysate enables presentation of a range of tumor antigens from a patient (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, autologous tumor cell lysate antigens presented to DCs stimulate specific CTL responses. 31,32,[36][37][38] …”
Section: Tumor Lysatesmentioning
confidence: 99%
“…[31][32][33] The first step in this process is providing DCs with tumor antigens. 34 Regardless of the method of tumor antigen delivery, there is convincing evidence for the induction of a protective and therapeutic antitumor immune response without specific toxicity.…”
Section: Sources Of Tumor Antigens To Prime Dcsmentioning
confidence: 99%
See 1 more Smart Citation